Pencegahan Penyakit Diabetes Mellitus melalui Pelatihan Pembuatan Jamu Saintifik bagi Warga Kecamatan Wonokromo Surabaya - Devyana Dyah Wulandari; Hotimah Masdan Salim; Andreas Putro Ragil Santoso; Endah Budi Permana Putri (Jurnal Surya Masyarakat, 2021)
Diabetes mellitus is a chronic disease caused by the pancreas not being able to produce enough insulin so that glucose levels in the blood cannot be controlled. Symptoms of this disease are characterized by polyuria, polydipsia, polyphagia and elevated blood glucose levels. Diabetes mellitus is a non-communicable disease that ranks 7th in the world's cause of death and Indonesia is a country with diabetes which is ranked 4th in the world. Prevention and treatment of diabetes mellitus patients can be done through various efforts, one of which is traditional herbal medicine. Therefore, the community development team held a training event for preparation scientific herbs in the context of preventing diabetes mellitus for residents of Wonokromo Surabaya. The results showed that there was an increase in public understanding about the dangers of diabetes mellitus with an increase in the average value from 45% to 90% and an increase in skills in preparation scientific herbal medicine from 40% to 95%. So it can be concluded that this activity brings very good benefits for the residents of Wonokromo Surabaya.